Pengaruh Latihan Eksentrik terhadap Performa Sepak Bola: Systematic Literature Review - Andri Suyoko; Suranta Pratama Ginting Manik; Ahmad Hafid Zakyyudin; Moh. Sofwan Attoilah (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This systematic review aims to evaluate the effects of eccentric resistance training on muscle strength and physical performance in football players. Modern football demands high neuromuscular capacity to generate and absorb force during sprinting and changes of direction (COD), making eccentric ability an important component of performance. The literature search followed PRISMA guidelines in Scopus, PubMed, and Web of Science for publications from 2020 to 2025, with PICOS-based criteria for male players from youth to professional levels. Seven studies met the inclusion criteria, with intervention durations of 4–12 weeks, including Nordic hamstring, flywheel inertial training, Copenhagen adduction, and eccentric free-weight training. The results showed consistent improvements in maximal strength, eccentric hamstring strength, and torque production. COD performance and countermovement jump (CMJ) also improved. However, sprint results were heterogeneous, influenced by acute muscle soreness and a lack of integration with speed-specific training. Overall, eccentric training is effective in improving neuromuscular capacity and is worth integrating into football conditioning programs. Further research is expected to explore optimal dose-response relationships and combinations of eccentric training methods.